Pembelajaran Model Reciprocal Teaching pada Siswa Kelas 4 Mata Pelajaran Matematika - Setiyawan, Hery; Nisa, Siti Hanifah Khairun; Irmawati, Mulya Fauzah; Santi, Tissa Laras (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the learning outcomes and student responses to the implementation of the Reciprocal Teaching learning model in fourth grade students. The Reciprocal Teaching model was chosen because it is considered capable of addressing students’ low computational comprehension skills through strategies such as summarizing, questioning, clarifying, and predicting the content of reading materials. The research method used is quantitative with a descriptive design. Data collection techniques involved evaluation tests and student response questionnaires. The research sample consisted of 9 students selected through stratified sampling based on their level of computational comprehension ability (high, medium, low). The data were analyzed using descriptive percentage analysis techniques. The results of the study show that the application of the Reciprocal Teaching model can improve students’ computational comprehension skills. This is evidenced by an increase in the average evaluation test score from 57 to 75 after implementing the learning model. In addition, the results of the student response questionnaire revealed that 80% of the students felt more motivated and found it easier to understand the material when using the Reciprocal Teaching model. These positive responses indicate that the Reciprocal Teaching model is not only effective in improving computational comprehension skills but also in enhancing students’ learning motivation. Therefore, the Reciprocal Teaching model can be considered an alternative instructional strategy that can be widely applied in elementary schools.